Standardization of Maturity at Harvest for Nectarine cvs. May Fire, Snow Queen, Silver King and Red Gold - Abrol, Ghan Shyam; Thakur, Kamal Singh; Thakur, Narayan Singh; Rana, Neerja (International Journal of Bio-resource and Stress Management, 2015)
The present investigations was conducted at the experimental orchard of Horticultural Research Station, Kandaghat district - Solan, Himachal Pradesh, India. during 2011 and 2012. An attempt was made to determine the optimum maturity for harvesting of nectarine cultivars May Fire, Snow Queen, Silver King and Red Gold on the basis of physico-chemical characteristics of the ripened fruit after a ripening period of 7 days under ambient conditions. For assessing maturity, fruits of each variety were harvested at three day intervals commencing from 6 days before the expected harvest date, with the last sampling date being 6 days after the expected harvest date. On the basis of physico-chemical characteristics the optimum time for harvesting of May Fire, Snow Queen, Silver King and Red Gold was found to be 68±3, 83±3, 83±3 and 89±3 days, from the date of full bloom, respectively. A significant increase in fruit size, weight, volume, pulp: stone ratio, TSS, sugar and carotenoid content was observed with advancement of harvesting period, while, a decrease in firmness, titratable acidity and ascorbic acid content. After a ripening period of 7 days fruits harvested on 3rd harvesting date retained better physico-chemical attributes in comparison to fruits harvested on other dates.